System zarządzania kryzysami Unii Europejskiej – znaczenie dla bezpieczeństwa międzynarodowego - Bryła, Jolanta (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
The rapid evolution of numerous contemporary threats and the development of multilateralism constitute two significant driving forces for the intensified cooperation between the European Union and the United Nations as regards crisis management. Responding to crises (threats), both natural and man-induced, in an efficient manner requires effective cri- sis management in order to take steps as early as possible when a threat emerges. Given the in- creasing external expectations in this field addressed at the EU, it has gradually been developing relevant civil as well as military instruments of crisis management and response. The EU has also been developing collaboration with the UN which calls for increased commitment of regional organizations in bearing the costs of maintaining international peace and security. Although this cooperation is mutually beneficial, it is not free from weaknesses and limitations on various levels of operation.
The European Union’s crisis management system – its significance for international security
Keywords: kryzys; zarządzanie kryzysami; Unia Europejska; Organizacja Narodów Zjednoczonych